Corrosion performance of Zn–Mg–Al coated steel in accelerated corrosion tests used in the automotive industry and field exposures. Issue 11 (11th March 2013) - LeBozec, N.; Thierry, D.; Peltola, A.; Luxem, L.; Luckeneder, G.; Marchiaro, G.; Rohwerder, M.
Abstract The corrosion performance of Zn–Mg(1–2%)–Al(1–2%) (ZMA) coatings has been compared to zinc–iron alloy (galvannealed, GA) and zinc–aluminum coating (Zn–5Al, Galfan) as well as to conventional zinc coatings produced by hot‐dip galvanization (HDG) and electrogalvanization (EG). For this purpose, cosmetic samples (painted and uncoated) and hem‐flange panels were produced. Their corrosion performance was compared in three different accelerated corrosion tests, as regularly used by the automotive industry, e.g., VDA621‐415, N‐VDA (VDA233‐102), and Volvo STD 423‐0014. As can be concluded from our results, the behavior of ZMA coatings was strongly dependent on the testing conditions as well as on the configuration of the samples. The advantageous effect of ZMA coating was more pronounced in open situations than in confined ones, irrespective of the testing conditions. ZMA coatings provided a significant improvement in comparison to conventional coatings in tests involving a significant salt load such as VDA621‐415 or neutral salt spray especially on cosmetic configurations. By contrast, the beneficial effect of ZMA coatings was less obvious in tests with lower salt load (VDA233‐102, Volvo STD423‐0014), particularly when considering cosmetic corrosion on painted samples and corrosion in confinement. Interestingly, no significant differences were observed between samples with varying Al and Mg content in the metallic coating (1–2% each). The results were compared to data from field exposure at stationary sites.